Kebutuhan Dan Faktor Kontekstual Komunikasi CSR Berbasis Web Pada Perusahaan Tambang Di Indonesia - Harmoni, Ati (Jurnal Manajemen, 2018)
Web-based CSR communications are based on management's need to have dialogue with various stakeholders of the company, internal and external. The purpose of this research is to know the management's view on the needs of web-based CSR communication. Interviews were conducted to key personnel from 3 leading mining companies in Indonesia who have an official web and have implemented CSR program. Management needs are then assessed using the framework of Media Richness Theory. Interview results show that there are factors that management considers to disclose CSR information on the web. Critical or non-critical the need ofmanagement for web-based CSR communications affects the appropriate level of use of web features. Communication needs that are considered critical will lead to the use of extensive web features or moderate and vice versa if management considers the need for web-based communication is non-critical then the use of web features is limited.Ã‚Â